2017
DOI: 10.1002/ana.24931
|View full text |Cite
|
Sign up to set email alerts
|

Global exosome transcriptome profiling reveals biomarkers for multiple sclerosis

Abstract: These data show that circulating exosomes have a distinct RNA profile in RRMS. Because putative targets for these miRNAs include the signal transducer and activator of transcription 3 and the cell cycle regulator aryl hydrocarbon receptor, the data suggest a disturbed cell-to-cell communication in this disease. Thus, exosomal miRNAs might represent a useful biomarker to distinguish multiple sclerosis relapse. Ann Neurol 2017;81:703-717.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 43 publications
6
119
0
Order By: Relevance
“…MS is thought to result from a complex interplay of genetic, epigenetic, and environmental risk factors . MicroRNAs (miRNAs) are epigenetic factors that have been investigated in MS, and over 170 miRNAs have been found to be differentially expressed in various tissues in either adult‐onset MS or experimental autoimmune encephalomyelitis (EAE) in mice . One study specifically compared miRNA expression levels in ped‐MS cases to pediatric controls, and 12 upregulated and one downregulated miRNA were reported .…”
Section: Introductionmentioning
confidence: 99%
“…MS is thought to result from a complex interplay of genetic, epigenetic, and environmental risk factors . MicroRNAs (miRNAs) are epigenetic factors that have been investigated in MS, and over 170 miRNAs have been found to be differentially expressed in various tissues in either adult‐onset MS or experimental autoimmune encephalomyelitis (EAE) in mice . One study specifically compared miRNA expression levels in ped‐MS cases to pediatric controls, and 12 upregulated and one downregulated miRNA were reported .…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory techniques such as quantitative PCR (qPCR), miRNA microarray, and deep sequencing (21) can be used for the early detection of expression profiling of miRNAs. To date, different studies have indicated that miRNA expression profiles could play a role as potential biomarkers for MS (22)(23)(24). Furthermore, miRNAs circulating in plasma have recently been shown to be differentially expressed in different stages of RRMS vs. secondary progressive MS, and they thus have been proposed to be an easily accessible blood-based biomarker to monitor MS (25).…”
mentioning
confidence: 99%
“…Recently, serum exosomal miRNA profiles of different disease were carried out. The miRNAs present varied greatly between different studies, ranging from 164 serum exosomal miRNAs in cancer patients to 584 distinct miRNAs in serum exosomes per normal sample (19)(20)(21). This phenomenon may be attributed to the different platforms used or to the specific physical environment created by specific diseases or conditions.…”
Section: Discussionmentioning
confidence: 99%